1996
DOI: 10.1053/jhep.1996.v24.pm0008903403
|View full text |Cite
|
Sign up to set email alerts
|

The central role of sinusoidal endothelial cells in hepatic hypoxia-reoxygenation injury in the rat

Abstract: Reperfusion injury is the phenomenon whereby relief of The role of individual cell types in hepatic hypoxiahypoxic ischemia is followed by accentuation rather than rereoxygenation (reperfusion) injury has not been comlief of tissue damage. This paradoxical event is well docupletely defined. We therefore examined the effects of mented in the intact liver and has considerable clinical relehypoxia and hypoxia-reoxygenation on the viability of vance in relation to organ preservation and hepatic surgery. SECs in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Nevertheless, our results show that Kuper cells were neither activated by cold preservation nor by changes in oxygen tension and temperature. Such ®ndings are in agreement with Samarasinghe and Farrell (1996), who reported that in vitro hypoxia-reoxygenation does not activate Kuper cells to secrete superoxide radicals or other cytotoxic products. Since protein synthesis is very sensitive to changes in oxygen tension (Lefebvre et al 1993), and because the level of ATP during cold storage is low, it is not surprisingly that protein synthesis rates were rather decreased after cold preservation.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, our results show that Kuper cells were neither activated by cold preservation nor by changes in oxygen tension and temperature. Such ®ndings are in agreement with Samarasinghe and Farrell (1996), who reported that in vitro hypoxia-reoxygenation does not activate Kuper cells to secrete superoxide radicals or other cytotoxic products. Since protein synthesis is very sensitive to changes in oxygen tension (Lefebvre et al 1993), and because the level of ATP during cold storage is low, it is not surprisingly that protein synthesis rates were rather decreased after cold preservation.…”
Section: Discussionsupporting
confidence: 92%
“…Rats were housed under constant temperature (22 8C) and humidity with a 12-h light/dark cycle, fed commercial rat pellets (Allied Foods, Sydney, Australia) and allowed food and water ad libitum. Liver cells were isolated by nonrecirculating collagenase perfusion of rat liver through the portal vein [17], as reported [10,16,18]. Viability (by trypan blue exclusion) always exceeded 80%.…”
Section: Hepatocyte Preparation Culture and Determination Of Viabilitymentioning
confidence: 99%
“…FcγRIIB -/-WT longed re-oxygenation [35][36][37]. Samarasinghe et al [36] compared in vitro the susceptibility of different liver cell types to hypoxia and found that SEC were even more resistant to prolonged hypoxic injury than hepatocytes or Kupffer cell.…”
mentioning
confidence: 99%
“…Samarasinghe et al [36] compared in vitro the susceptibility of different liver cell types to hypoxia and found that SEC were even more resistant to prolonged hypoxic injury than hepatocytes or Kupffer cell. In their study only 10% of SEC underwent cell death despite 24 h hypoxia (PO 2 <1 mm Hg), and even after 8 h hypoxia and 24 h of re-oxygenation only 40% of the SEC expressed features of necrotic cell death.…”
mentioning
confidence: 99%